Pathological Aspects of COVID-19 as a Conformational Disease and the Use of Pharmacological Chaperones as a Potential Therapeutic Strategy - Aoe, Tomohiko (Frontiers in Pharmacology, 2020)
Coronavirus disease 2019 (COVID-19), the seventh human coronavirus infectious disease, was first reported in Wuhan, China, in December 2019, followed by its rapid spread globally (251,059 deaths, on May 5, 2020, by Johns Hopkins University). An early clinical report showed that fever, cough, fatigue, sputum production, and myalgia were initial symptoms, with the development of pneumonia as the disease progressed. Increases in the level of serum liver enzymes, D-dimer, cardiac troponin I, and creatinine have been observed in severely ill patients, indicating that multiple organ failure had occurred in these cases. Lymphopenia and an increase in IL-6 were also observed. Although COVID-19 patients are administered glucocorticoid therapy to treat the excessive immune response to SARS-CoV-2 infection, the efficacy of this form of therapy is unclear. Viremia is observed in severe cases, suggesting that in addition to type 2 alveolar epithelial cells, many cell types, such as vascular endothelial cells, cardiomyocytes, renal tubular cells, neuronal cells, and lymphocytes, may be damaged. The improvement of survival rates requires elucidation of the mechanism by which cellular damage occurs during viral infection. Cellular therapy, along with organ support systems such as oxygen therapy, artificial ventilation, extra corporeal membrane oxygenation and dialysis, as well as antiviral therapy, are required. Viral replication in infected host cells may perturb protein folding in the endoplasmic reticulum (ER), causing ER stress. Although an adaptive cellular response, i.e. the unfolded protein response, can compensate for the misfolded protein burden to some extent, continued viral proliferation may induce inflammation and cell death. Therefore, we propose that proteostasis dysfunction may cause conformational disorders in COVID-19. The application of pharmacological chaperone therapy to treat COVID-19 patients is additionally discussed.